OPTIMASI PENGGUNAAN KARBOPOL DAN Na CMC PADA FORMULA GEL EKSTRAK ETANOL DAUN KAYU PUTIH (Melaleuca leucadendra L.)DENGAN METODE SIMPLEX LATTICE DESIGN - Arum Kavita Sari; Dwi Saryanti (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
Eucalyptus leaves (Melaleuca leucadendra L.) are a type of plant that has antibacterial properties for Klebsiella pneumoniae, which is a bacteria that causes respiratory tract infections (ISPA). Eucalyptus leaves have active compounds thought to have Klebsiella pneumoniae antibacterial activity, namely flavonoids and phenolic, in the ethanol extract of eucalyptus leaves with a concentration of 20%. The gel preparations have the advantage of being easy to dry out, forming a film layer that is easy to wash and gives a cool feeling to the skin. This study aims to make an optimal eucalyptus leaf ethanol extract gel formula with variations of carbopol and Na-CMC optimally using the Simplex Lattice Design (SLD) method. Eucalyptus leaf extraction used the maceration method with 70% ethanol solvent. Determination of the optimal formula using the Simplex Lattice Design (SLD) method using Design Expert 10 software with test parameters for pH, viscosity, adhesion and dispersion power. Verification of the optimal formula used the One sample t-test, and the stability test was carried out using the freeze-thaw method. This study provides optimal formula results with a ratio of 38% carbopol gel base and 62% Na-CMC. The results of the verification test show that the prediction results with the test results are not significantly different, indicated by a p value> 0.05, this shows that the formula for the results of the Simplex Lattice Design (SLD) method is valid as expected including organoleptic, homogeneity, pH, viscosity, adhesion, and power. spread.